2023
DOI: 10.1007/s13205-023-03631-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune-adjuvant effect of vitamin A and probiotics supplementation on humoral response to cell culture rabies vaccine in rabbits

Abstract: This study was carried out to evaluate the effects of vitamin A (Vit A) and probiotic co-supplementation with rabies vaccine on humoral immune response in New Zealand white (NZW) rabbits. For this experiment, 54 rabbits were randomized into six experimental and three control groups. Mixed cultures of commercial probiotics supplements and a dose of Vit A were administered to each animal. Results were compared with the control group fed with only basal diet. Animals in different treatment groups showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A similar response was found after 35 days, suggesting that ID immunization was noninferior. Moreover, all the rabbits were given high vitamin-rich probiotic dietary supplementation, contributing to the improved humoral response [15][16][17][18][19][20]. It was reported that ID immunization, even with a low dose, delivers antigen directly to the area that contains a high number of antigen-presenting cells (APCs), thus producing higher antibody titers than the previously used IM vaccination regimen.…”
Section: Resultsmentioning
confidence: 99%
“…A similar response was found after 35 days, suggesting that ID immunization was noninferior. Moreover, all the rabbits were given high vitamin-rich probiotic dietary supplementation, contributing to the improved humoral response [15][16][17][18][19][20]. It was reported that ID immunization, even with a low dose, delivers antigen directly to the area that contains a high number of antigen-presenting cells (APCs), thus producing higher antibody titers than the previously used IM vaccination regimen.…”
Section: Resultsmentioning
confidence: 99%